Charles E. Burchfield : the sacred woods - Weekly, Nancy (State University of New York Press, 1993)
Charles E. Burchfield: The Sacred Woods explores the underlying spirituality of American painter Charles E. Burchfield (1893-1967). Author Nancy Weekly, the Charles Cary Rumsey Curator of the Burchfield Art Center, traces the evolution of his art and philosophical fluctuations. She identifies his affinity for developments in 19th century art and literature, including pantheism, luminism, romanticism, and transcendentalism. The book celebrates the 100th anniversary of Burchfield's birth. It is complemented by 40 color plates and 60 black and white illustrations.